(untitled) (Journal of actual problems of jurisprudence, 2019)
History customary law of the Kazakh evidence of active participation of the Kazakh people in the development of world civilization. In Kazakhstan, there is a constant change and confusion of some aspects and whole strata of the law of different nations and cultures.